Pengaruh Customer Value Terhadap Kepuasan Pengguna Smartphone Blackberry Gemini Curve 8520 (Studi pada Mahasiswa Fakultas Ekonomi Universitas Trunojoyo Madura) - Miftahul Jannah; Muh. Syarief; Bambang Setiyo Pambudi (Jurnal Studi Manajemen dan Bisnis, 2014)
The purpose of this study were to find the influence of Customer Value was consist of Functional value (quality/performance) (X1), emotional value (X2), functional value price/ value for money (X3), and social value (X4) towards satisfaction (Y) and also to find the biggest variable effect towards college students user satisfaction at Economy Faculty Trunojoyo Madura University. The Population of this study was college students at Economy Faculty Trunojoyo Madura University. The Method used in this research was the purposive sampling, by 50 respondents and the research done in November 2013. The data collecting method were collecting kuesioner and library research. The result of this study were the Functional value (quality/performance) (X1), emotional value (X2), functional value price/ value for money (X3), dan social value (X4) effected the satisfaction (Y) of college students user smartphone Blackberry Gemini Curve 8520 at Economy Faculty Trunojoyo Madura University. The result from t test (parsial) proved the Functional value (quality/performance) (X1), emotional value (X2), price/ value for money (X3) had an signifikant effect to satisfaction (Y), while social value hadn’t signifikant effect towards satisfaction (Y) of college students user smartphone Blackberry Gemini Curve 8520 at Economy Faculty Trunojoyo Madura University. It could be concluded that from fourth free variable which have bigger influence to satisfaction (Y) of college students user smartphone Blackberry Gemini Curve 8520 at Economy Faculty Trunojoyo Madura University is functional value price/ value for money (X3).